Geochemical, mineralogical and toxicological characteristics of coal fly ash and its environmental impacts. (November 2022) - Gopinathan, P.; Santosh, M.S.; Dileepkumar, V.G.; Subramani, T.; Reddy, Roopa; Masto, R.E.; Maity, Sudip
Abstract: Coal and coal-based products (by-products), along with other fossil fuels should be used with caution because of their impact on human health and the global climate. In the light of the environmental impact these fossil fuels cause, it's essential to understand the elemental configuration of coal-derived samples and their impact on the ecosystem. Some reports in past have described, geochemical and mineralogical physiognomies of fly-ash and their impact on the environment. However, a comprehensive investigation of various aspects of fly ash like geochemistry, mineralogy, morphology, and toxicological effects has been very sparse and the present study reports the above aspects. The ICP-OES studies confirm the presence of various elements (Al, Ca, Fe, Mg, Na, P, S, Si, and Ti) in the samples. The XRD analysis exposed the presence of minerals like Quartz, H-Hematite, Anatase, Muscovite, and Rutile, in addition to the various phases such as amorphous and crystalline in the fly-ash. Specific samples also possessed Ilmenite which is uncommon in many other samples. Chromium and lead, the well-known heavy metals to cause soil and water pollution in the neighbourhood were found to be existing in higher concentrations in the fly-ash samples, whereas cadmium was found to be the least among the toxic elements found in the samples. The samples were subjected to FE-SEM analysis, which reveals the presence of irregularly shaped minerals and unburnt carbon known to reduce the burning efficiency of coal, especially in power plants. Toxicology studies reported in the work suggested that fly-ash is toxic to the environment at higher concentrations than at lower concentrations. Graphical abstract: Image 1 Highlights: Coal Fly Ash samples have been characterized for geochemical, mineralogical and toxicological properties. Environmental impacts of coal fly ash from coal-fired power plants have been reported. Various elements and their oxides in amorphous and crystalline forms are part of fly ash samples. Higher concentrations of the heavy metals in fly ash samples appear to be toxic.